Renal extramedullary hematopoiesis as an epiphenomenon of bone marrow dysfunction in a patient with primary myelofibrosis: A rare case report - Corrado Ini’, MD; Pietro Valerio Foti, PhD; Andrea Duminuco, MD; Renato Farina, MD; Mariangela Clemenza, MD; Francesco Tiralongo, MD; Emanuele David, MD; Stefano Palmucci, PhD; Giuseppe Alberto Palumbo, PhD; Antonio Basile, PhD (Radiology Case Reports, 2024)
Extramedullary hematopoiesis represents a clinical compensatory condition characterized by the growth of hematopoietic tissue outside the bone marrow. It can mainly occur in patient with myeloproliferative disorders where alteration or neoplastic invasion of the bone marrow causes ineffective production of blood cells with the recruitment of progenitrix blood cells in non-hematopoietic organs, including kidneys. Renal extramedullary hematopoiesis is a rare condition manifesting as parenchymal or perirenal soft tissue masses with different patterns mimicking neoplasms, infectious or vascular diseases. We describe a unique case of a patient affected by primary myelofibrosis underwent ultrasound and magnetic resonance examinations showing bilateral perirenal alterations to be related to hemopoietic tissue. We also focused on the pathophysiology of this condition with imaging correlation. The case we present emphasises the importance of recognising the main radiological features of renal extramedullary hematopoiesis. MR examination should become part of the diagnostic pathway of the patient with primary myelofibrosis.